PENGARUH BAHAN BAKAR PERTAMAX DAN PERTALITE TERHADAP MOBIL HEMAT ENERGI “HAIZUM “ - Fahrizal amin, Achmad Nauvalil (Jurnal Teknik Mesin, 2020)
ABSTRAKTransportation in the Globalization era focuses on fuel efficiency that is efficient or environmentally friendly, therefore a KMHE event is held which aims to encourage the creation of a transportation that has good fuel efficiency. This study aims to determine effect use of pertamax and Pertalite fuels on energy-efficient cars "Haizum" and calculate the AFR and heating values of the two fuels. This test is done manually and to find out which fuel is more efficient at variations in engine speed in the numbers 4000 - 5500 RPM with a distance of 150 M to get a comparison of specific fuel consumption. results fuel consumption of Pertamax better than pertalite seen from the heating value of HHV and LHV, this shows that the fuel of Pertamax is better because the higher HHV value, the lower exhaust emissions due to the high HHV value indicates all condensed fuel becomes liquid so that little exhaust gas emissions. The AFR value indicates the number 15: 1 which means that the fuel which is misted is burning completely in the combustion chamber.